Case Report: Successful Rescue Therapy of Extensively Drug-Resistant Acinetobacter baumannii Osteomyelitis With Cefiderocol. (5th May 2020) - Dagher, Michael; Ruffin, Felicia; Marshall, Steven; Taracila, Magdalena; Bonomo, Robert A; Reilly, Rachel; Fowler, Vance G; Thaden, Joshua T
Abstract: Cefiderocol is a novel catechol siderophore cephalosporin antibiotic developed to treat resistant gram-negative infections. We describe its successful use as rescue therapy, combined with surgical debridement, to treat a patient with osteomyelitis due to extensively drug-resistant Acinetobacter baumannii. Bacterial whole-genome sequencing identified the strain and antibiotic resistance determinants. Abstract : Cefiderocol is a novel catechol siderophore cephalosporin developed to treat resistant gram-negative infections. We report its successful use in conjunction with surgical debridement to treat osteomyelitis due to extensively drug-resistant Acinetobacter baumannii. Bacterial genome sequencing revealed the determinants of resistance.